An evaluation of risk management stratergies in academic libraries in Oyo State, Nigeira (2012)
This study investigated the risks and risk management strategies adopted in selected academic libraries in Oyo state. A structured questionnaire was developed to elicit information from 60 respondents selected randomly from four academic libraries in the state. The study sought to provide answers to four research questions raised. Simple percentages were used to analyze the data obtained. The findings showed that fire outbreak, building collapse,flooding as well as risks associated with users top the list of risk factors and that risk management policies were not adequately provided in the surveyed libraries. Based on the findings, recommendations were mae that risk management be incorporated into the strategic and operational planning processes at all levels of academic libraries and that risk assessments be conducted on all new equipment and facilities and that risks should be identified, reviewed and monitored on an ongoing basis at nominated levels within library system.